2014
DOI: 10.1128/jcm.03483-13
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Aerobic Gram-Positive Bacilli by Use of Vitek MS

Abstract: The accuracy of Vitek MS mass spectrometric identifications was assessed for 206 clinically significant isolates of aerobic Grampositive bacilli representing 20 genera and 38 species. The Vitek MS identifications were correct for 85% of the isolates (56.3% to the species level, 28.6% limited to the genus level), with misidentifications occurring for 7.3% of the isolates. I dentification of aerobic, Gram-positive bacilli (GPB) to the species level is challenging. Biochemical methods are slow and labor-intensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Many studies find multi-drug resistant strains, though [14]. A recent study which included a large number of isolates (n = 179) found 72% isolates to be resistant to all oral antimicrobials [15]. All our isolates were multidrug resistant sensitive to only Linezolid and vancomycin.…”
Section: Discussionmentioning
confidence: 53%
“…Many studies find multi-drug resistant strains, though [14]. A recent study which included a large number of isolates (n = 179) found 72% isolates to be resistant to all oral antimicrobials [15]. All our isolates were multidrug resistant sensitive to only Linezolid and vancomycin.…”
Section: Discussionmentioning
confidence: 53%
“…Another VITEK MS-Automated Testing also showed misidentifications of two C. afermentans isolates as Lactobacillus species (Navas et al 2014). Moreover, C. ureicelerivorans and C. minutissimum were also misidentified as C. mucifaciens and C. aurimucosum, respectively (Navas et al 2014). To the best of our knowledge, there is no report about misidentifications of 2 C. argentoratense isolates as C. diphtheriae by VITEK 2 ANC-Automated Testing.…”
Section: Resultsmentioning
confidence: 95%
“…A multicenter study reported that identification by VITEK 2 using clinical isolates showed 4.9% low discrimination, 4.6% incorrect identification, and 0.3% unidentified isolates, and the results of Corynebacterium identification showed misidentification of C. urealyticum strain from 51 Corynebacterium species (not included C. argentoratense) (Rennie et al 2008). Another VITEK MS-Automated Testing also showed misidentifications of two C. afermentans isolates as Lactobacillus species (Navas et al 2014). Moreover, C. ureicelerivorans and C. minutissimum were also misidentified as C. mucifaciens and C. aurimucosum, respectively (Navas et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…As MALDI-TOF MS is reported to be widely used in routine laboratories (20)(21)(22)(23). The most prominent advantages are its speed and low running costs provided that a quality-controlled database of reference spectra including all relevant microorganisms is available (3).…”
Section: Discussionmentioning
confidence: 99%